Ocean mass, sterodynamic effects, and vertical land motion largely explain US coast relative sea level rise - T. C. Harvey (Nature Portfolio, 2021)
Tide gauge observations of relative sea-level trends between 1993 and 2018 around the contiguous United States can largely be attributed to a combination of changes in ocean mass, sterodynamic effects and vertical land motion, according to a sea-level budgeting exercise.